Management of Flow Reversal in Patients With Atrial Shunts Implanted to Reduce Left Atrial Pressure - Hidenori Yaku, MD, PhD; Jean-Christophe Eicher, MD; Martin W. Bergmann, MD; Tobias Kister, MD; Tudor C. Pörner, MD; Barry A. Borlaug, MD; Rajeev C. Mohan, MD; Matthew Price, MD; Jan Komtebedde, DVM; Sanjiv J. Shah, MD (JACC: Case Reports)
This case series presents 6 patients with heart failure (HF) and preserved or mildly reduced ejection fraction who underwent atrial shunt implantation in a clinical trial evaluating its safety and efficacy. Shunt closure was considered in selected cases of worsening HF, particularly when shunt flow reversal was observed. Detailed hemodynamic evaluation revealed that shunt closure may have been detrimental in 5 cases and beneficial in only 1 case. Intentional closure of an implanted atrial shunt has not been previously reported; here, we describe the clinical decision-making process and outcomes based on comprehensive hemodynamic assessments, including pulmonary vascular dynamics and shunt flow patterns in such cases. These findings highlight the critical importance of thorough hemodynamic evaluation in patient management after atrial shunt placement in recognition of other factors that may play a role in the presence of the shunt. Additional research is needed to establish optimal management strategies for patients experiencing worsening HF after atrial shunt implantation.